Thyroid Function Affects the Risk of Post-stroke Depression in Patients With Acute Lacunar Stroke - Guo, Jianglong; Wang, Jinjing; Xia, Yue; Jiang, Shiyi; Xu, Pengfei; Tao, Chunrong; Sun, Wen; Liu, Xinfeng (Frontiers in Neurology, 2022)
Objective This study aimed to investigate whether thyroid function profiles are associated with post-stroke depression (PSD) and evaluate the mediation effect of cerebral small vessel disease (cSVD) on the association of thyroid function profiles and PSD in patients with acute ischemic lacunar stroke. Methods In this study, 372 patients with confirmed acute ischemic lacunar stroke within 3 days of onset were consecutively recruited. Serum levels of thyroid hormones and thyroid antibodies were detected on admission. Lacunar infarcts, white matter lesions, cerebral microbleeds, and enlarged perivascular spaces were rated using validated scales. The severity of depression was scored with the 24-item Hamilton Depression Scale in the hospital after a week of stroke onset. Multivariate regression was utilized to analyze the association of thyroid function profiles and PSD. Mediation analysis was employed to evaluate the effect of cSVD on the association of thyroid function profiles and PSD. Results A total of 87 (23.4%) participants were diagnosed with depression after stroke. Serum thyroid-stimulating hormone (TSH) levels were significantly higher in patients with PSD than in those without PSD, while free triiodothyronine (FT3) and free thyroxine (FT4) were not significantly different between the two groups. After adjusting for potential confounders, serum TSH levels were positively associated with the risk of PSD (OR = 1.228; 95% CI: 1.053–1.431, p = 0.009). A similar association was also found between the total cSVD burden score and PSD (OR = 2.137; 95% CI: 1.634–2.793, p < 0.001). Further mediation analysis indicated that 26.37% of the association between TSH and PSD was mediated by cSVD. Conclusions Serum TSH levels on admission can probably predict depression after acute ischemic lacunar stroke.